In-silico Sequence Alignment, Phylogeny, Docking, and Domain Analysis of Fatty Acid Desaturase (FAD) Proteins in Pearl Millet (Pennisetum glaucum L.) - Vasanthrao, Thalari; Moin, Mazahar; Kona, Prabhavathi; Tyagi, Wricha; Gupta, S. K.; Sudhakar, Reddy P.; Danam, Shashi Bhushan (International Journal of Bio-resource and Stress Management, 2025)
This in-silico analysis was conducted during May and June, 2025 at ICRISAT, Patancheru, Telangana, India to explore the properties of pearl millet FAD (fatty acid desaturase) proteins. The protein sequences were retrieved from the NovoGene Millet database, and analyzed using ExPASy ProtParamto investigate the FAD protein family in pearl millet. Phyre2.1 was used to predict the secondary structures, and protein phylogeny was analyzed using ClustalW to identify evolutionary relationships. Conserved motifs were identified using the MEME online tool. Multiple sequence alignment of PgFAD protein sequences across six genotypes in the pangenome was performed through ClustalW to identify the polymorphism. A total of 22 PgFAD proteins were identified, and their physiochemical analysis revealed diverse molecular weights, isoelectric points (pI) and hydrophobicity profiles, suggested functional variability. Three-dimensional secondary structure analysis revealed that all PgFADs are rich in alpha helical content (45–66%), suggesting a compact, stable and membrane spanning structure. Low to moderate disordered regions (6 to 22%) in these proteins indicated their enzymatic activities. Protein polymorphism analysis showed that PgFAD-5e and PgFAD-6c are conserved across all six genotypes in the pangenome, whereas PgFAD-5c, PgFAD-5f and PgFAD-1w6 exhibited multiple nonsynonymous mutations particularly in PI526529 genotype. These findings provided insights into the structural and functional diversity of fatty acid desaturases and established a foundation for targeting these genes to enhance lipid stability and improve quality-related traits of pearl millet.